Uniform selenization of crack-free films of Cu(In,Ga)Se2 nanocrystals - Harvey, Taylor B. (2019)
Crack-free films of Cu(In,Ga)Se2 (CIGS) nanocrystals were deposited with uniform thickness (>1 μm) on Mo-coated glass substrates using an ink-based, automated ultrasonic spray process, then selenized and incorporated into photovoltaic devices (PVs). The device performance depended strongly on the homogeneity of the selenized films. Cracks in the spray-deposited films resulted in uneven selenization rates and sintering by creating paths for rapid, uncontrollable selenium (Se) vapor penetration. To make crack-free films, the nanocrystals had to be completely coated with capping ligands in the ink. The selenization rate of crack-free films then depended on the thickness of the nanocrystal layer, the temperature, and duration of Se vapor exposure. Either inadequate or excessive Se exposure leads to poor device performance, generating films that were either partially sintered or exhibited significant accumulation of carbon and selenium. The deposition of uniform nanocrystal films is expected to be important for a variety of electronic and optoelectronic device applications.